2014
DOI: 10.1016/j.jaa.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Violence among foragers: The bioarchaeological record from central California

Abstract: a b s t r a c tSpatial and diachronic patterns in skeletal evidence for three forms of violence were evaluated for central California with information from a bioarchaeological database that contains information on 16,820 buri als from 329 sites. The most abundant form of violence was sharp force/projectile trauma (462/6278, 7.4%), followed by blunt force craniofacial trauma (264/6202, 4.3%) and trophy-taking/dismemberment (87/12,603, 0.7%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…The archaeological correlates of the MCA across California have been identified as disruptions in exchange systems (Arnold, 1992;Gilreath and Hildebrandt, 1997;Jones et al, 1999), subsistence shifts (Collins, 2010;Kennett and Kennett, 2000), altered settlement patterns (Gardner, 2006;Hull, 2007;Jones and Ferneau, 2002), and higher levels of disease, undernutrition, and violence (Andrushko et al, 2005;Jones and Schwitalla, 2008;Lambert, 1994Lambert, , 1997Pilloud et al, 2014;Raab and Larson, 1997;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The archaeological correlates of the MCA across California have been identified as disruptions in exchange systems (Arnold, 1992;Gilreath and Hildebrandt, 1997;Jones et al, 1999), subsistence shifts (Collins, 2010;Kennett and Kennett, 2000), altered settlement patterns (Gardner, 2006;Hull, 2007;Jones and Ferneau, 2002), and higher levels of disease, undernutrition, and violence (Andrushko et al, 2005;Jones and Schwitalla, 2008;Lambert, 1994Lambert, , 1997Pilloud et al, 2014;Raab and Larson, 1997;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has used the Central California Bioarchaeological Database (CCBD) to assess the impacts of the MCA on rates of nutritional stress, disease, and interpersonal violence in Central California regions, including the San Francisco Bay Area, Delta, and Central Valley (Jones and Schwitalla, 2008;Pilloud, 2006;Pilloud et al, 2014;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014). These studies found higher frequencies of skeletal pathologies like cribra orbitalia, porotic hyperostosis, and enamel hypoplasia attributable to disease and malnutrition, in addition to increased rates of pre-and perimortem sharp and blunt force trauma indicative of violence, during the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for our tobacco-using woman from CA-SCL-919, osteological analyses determined she was a "middleaged adult" most likely between 35 and 44 years. Based on osteological analyses of skeletal populations from archaeological sites, the average life expectancy of pre-contact native Californians was under 30 years, when all individuals including sub-adults are included in the calculation (e.g., Bartelink, 2009;Jurmain et al, 2009;Schwitalla et al, 2014). Life expectancy still averages around 40 years when subadults are removed from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that females were not victims of interpersonal violence. Indeed, Schwitalla et al (2014) record many examples of skull depressions, ulnar fractures (speculated to represent "parry fractures"), and projectile wounds …”
mentioning
confidence: 99%
“…Likewise, Heizer (1949) thought that a calotte (skull cap) fashioned into a container from the same site was that of an "enemy, " and Ragir (1972:25) interpreted five isolated skulls from CA-SAC-168 as "heads taken from war victims." Isolated heads have also been reported from sites that post-date the Early period, including CA-SMA-23, CA-SAC-99, and CA-SCL-806 (Schwitalla et al 2014). In addition, headless burials have also been found and implicated in ancient trophy-taking behaviors.…”
mentioning
confidence: 99%